Estimation of the standard surgical times of the most common general surgery procedures and the probability of extending them to make surgery scheduling more efficient - Pérez Ruiz, Manuel David (2024)
Objective: To determine the standard surgical times of the four most common general surgery procedures (unilateral inguinal hernioplasty, bilateral inguinal hernioplasty, umbilical hernioplasty and cholecystectomy) in a second-level hospital and to estimate the probability of extending the time of each of the procedures. Efficiency is a widely studied subject in economics. It involves the need for fewer elements in the production of a certain level of goods and services. Therefore, it is extremely important to consider it in the field of surgery. Materials and methods: An observational, descriptive and retrospective study. It used the operating room records from 2017 to 2019 of the General Surgery service in a second-level hospital. Based on this information, the time required for each procedure was standardized using the mean for each one (umbilical hernioplasty, unilateral or bilateral inguinal hernioplasty and cholecystectomy). The probability of extending surgical times was estimated based on the obtained data and confidence interval. Results: The mean for unilateral inguinal hernioplasty was 76 min (95.00 % CI: 72-80 min, SD 23), for bilateral inguinal hernioplasty 104.38 min (95.00 % CI: 91-116 min, SD 41.7), for umbilical hernioplasty 59.31 min (95.00 % CI: 54-63 min, SD 29.99) and for cholecystectomy 85.735 min (95.00 % CI: 83-88 min). The probability of scheduling three surgical interventions and completing all of them on time (upper limit of the CI) is 92.69 %, and the probability of scheduling three surgical interventions and extending the time of all of them is 0.0016 % (lower limit of the CI). Conclusions: Planning scheduled operations using standardized surgical times is feasible. Updated statistics on surgical procedures (average time for each procedure) are required since it is possible to more accurately detect and supervise operating room dynamics by identifying opportunity areas. This will make operating room time more efficient for the benefit of health care systems and patients.